Ultrastructural damage in coffee seeds exposed to drying and to subzero (°C) temperatures - Coelho, Stefânia Vilas Boas; Rosa, Sttela Dellyzete Veiga Franco da; Lacerda, Laura Nardelli Castanheira; Clemente, Aline da Consolação Sampaio; Silva, Luciano Coutinho; Fantazzini, Tatiana Botelho; Ribeiro, Fernando Sales; de Melo Castro, Elisa (Coffee Science - ISSN 1984-3909, 2020)
During drying and freezing, protective mechanisms act to maintain seed physiological quality. Some of these mechanisms contribute to the integrity of cell membranes. The damage caused to cell membranes due to cell stress can be seen in ultrastructural studies. The aim of this study was to investigate ultrastructural changes in endosperm cells of coffee seeds brought about by drying and by exposure to low temperatures. Seeds of Coffea arabica were dried in silica gel to moisture contents of 40, 20, and 5 % (wb) and brought to equilibrium at temperatures of 10, -20, and -86oC. Germination, vigor, and tetrazolium tests were performed for evaluation of seed physiological quality. Ultrastructural damage was analyzed by scanning electron microscopy. Coffee seeds with 40% moisture content have whole, swollen, and expanded cells, with a filled lumen and without signs of damage. The physiological and ultrastructural quality of seeds exposed to below zero temperatures with 40% moisture content is compromised. They have null germination and empty cells, indicating leakage of cell content. Drying of coffee seeds leads to uniform contraction of inner cell content. Drying of coffee seeds to 5% moisture content leads to intense contraction of cell volume, with physiological and ultrastructural damage. Key words: Scanning electron microscopy; desiccation tolerance; Coffea arabica L.